Randomized, Controlled Comparison of Advanced Hemostatic Pads in Hepatic Surgical Models. (4th March 2014) - Lewis, Kevin M.; McKee, Jeff; Schiviz, Alexandra; Bauer, Alexander; Wolfsegger, Martin; Goppelt, Andreas
Abstract : Blood loss during hepatic surgery leads to poor patient outcomes. This study investigates the hemostatic efficacy of a novel sealing hemostatic pad (polyethylene glycol-coated collagen, PCC) and a fibrin sealant pad (fibrin-thrombin coated collagen, FTC) in a leporine hepatic segmentectomy and a porcine hepatic abrasion model. A segmentectomy was used to compare hemostatic success and hematoma incidence in 20 rabbits (10/group). Hepatic abrasions were used to compare hemostatic success up to 10 min after application in six pigs (42 lesions/group). In the segmentectomy model, PCC achieved 100% hemostatic success within 2 min (95% CI: 72.3% to 100%) and FTC achieved 80% hemostatic success within 3 min (49.0% to 94.3%). PCC had lower hematoma incidence at 15 min (0.0 versus 11.1%) and 24 h (20.0 versus 66.7%). In the abrasion model, PCC provided superior hemostatic success at 3 (odds ratio: 24.8, 95% CI: 8.86 to 69.2, P < 0.001 ), 5 (66.3, 28.5 to 153.9, P < 0.001 ), 7 (177.5, 64.4 to 489.1, P < 0.001 ), and 10 min (777.6, 148.2 to 4078, P < 0.001 ) leading to statistically significant less blood loss. The novel sealing hemostat provides faster and more sustained hemostasis than a fibrin sealant pad in a leporine hepatic segmentectomy and a porcine hepatic abrasion model of hepatic surgery.